Pencatatan Nikah Sirri dalam Perspektif Hukum Islam: Studi Kasus di Kecamatan Sungai Raya Kepulauan Kabupaten Bengkayang - S, Sartini (Media Hukum Indonesia (MHI), 2026)
Unregistered marriage (nikah sirri) is a social phenomenon that frequently occurs in Sungai Raya Kepulauan District, Bengkayang Regency. This practice is considered religiously valid because it fulfills the pillars and requirements of marriage, but is not officially registered at the Office of Religious Affairs (KUA). This research aims to analyze the perspective of Islamic law regarding the registration of unregistered marriages, identify its impact on the rights of women and children, and evaluate the factors influencing the prevalence of this practice. The research employs a qualitative method with a descriptive-analytical approach. Data was collected through in-depth interviews with couples practicing unregistered marriage, religious figures, the head of KUA, and local community members. The research findings indicate that from the perspective of Islamic law, unregistered marriage is considered valid if its pillars and conditions are fulfilled, but marriage registration is very important as a form of maslahah mursalah to protect family rights. The negative impacts include uncertainty regarding the legal status of wives and children, difficulties in obtaining inheritance rights, and minimal legal protection. Factors driving the practice of unregistered marriage include economic aspects, low legal understanding, local cultural influences, and limited access to official registration.